Local bond average for the size and temperature dependence of elastic and vibronic properties of nanostructures. (20th May 2009) - Gu, Mingxia; Sun, Chang Q.; Tan, Cher Ming; Wang, Shanzhong
With the miniaturisation of a solid down to nanometre scale, the mechanical and optical properties of such nanomaterials are different from those of their corresponding bulk materials. A systematic understanding of the atomic origin of the unusual behaviour of mechanical and optical properties of a nanosolid is presented here towards the predictions for design and controllable growth of nanostructured materials. The Local Bond Average (LBA) approximation and Bond-Order-Length-Strength (BOLS) correlation mechanism in size, temperature and pressure domain have been developed, which enables the tunability of various measurable properties, such as elastic constants, and optical phonon frequency shift. Agreement between predictions and observations reveals that the shortened and strengthened surface bonds are responsible for the observed size dependent change of material properties, while the temperature induced bond expansion and weakening are the physical origin for the temperature dependent change of measurable material properties.